Pemanfaatan Media Youtube Sebagai Media Sosio Edukasi Terhadap Mahasiswa Universitas Syiah Kuala - Subhan Zuhdi; Dara Fatia (PT Riset Mandiri Nusantara, 2025)
The Youtube platform has great benefits and influence on learning at this time because this platform has a variety of information from all fields available at this time. The purpose of this research is to find out how the utilization of Youtube media as a Socio-Educational media for Syiah Kuala University Students. The research method used in this research is qualitative with a descriptive approach. The theory used in this research is Anthony Giddens' Structuration theory. The results of this study concluded that students utilize the Youtube Platform as a learning medium because Youtube is a flexible platform, allowing students to access the platform anywhere and anytime without having to be limited by learning sessions. The types of content that are spread are diverse, making it easier for students to get learning according to the fields they want to learn. Youtube Content Creator explains the material through the Channel by using animation and audio visuals so as to make learning fun and not monotonous. Students use Youtube to deepen their understanding of the material taught in class and outside of class because of the various types of information and delivery that are interesting and easy for students to understand.